A comprehensive analysis of mathematical resilience in elementary school students: A gender and learning style perspective - Siagian, Muhammad Daut; Ade Evi Fatimah; Agung Prasetyo Abadi; Sutirna; Siregar, Rosliana (Beta: Jurnal Tadris Matematika, 2025)
[English]: This study investigates the relationship between students' mathematical resilience and their learning styles and gender. Employing a non-experimental comparative design and survey methodology, the study utilized mathematical resilience and learning style questionnaires as data collection instruments. The study's sample consisted of 62 fifth-grade elementary school students from Stabat City, North Sumatra Province. Sampling was conducted using the probability proportional sampling technique, resulting in 32 female and 30 male students. Data analysis employed a two-way ANOVA test to examine the impact of two independent variables (learning style and gender) on the dependent variable (mathematical resilience). The findings revealed that the visual learning style was the predominant learning style among students. Furthermore, the study demonstrated a significant correlation between learning styles and mathematical resilience, suggesting that variations in learning styles significantly influence mathematical resilience. In contrast, gender was found to have no discernible impact on mathematical resilience. Additionally, the analysis indicated no interaction between learning style and gender in influencing mathematical resilience. These findings imply that learning styles independently influence mathematical resilience, without any moderating effect of gender. The implications of this study suggest that when developing teaching strategies to enhance mathematical resilience, it is advisable to prioritize individual learning styles rather than differentiating based on gender. [Bahasa]: Penelitian ini bertujuan untuk menguji resiliensi matematis siswa dalam kaitannya dengan gaya belajar dan jenis kelamin mereka. Dengan menggunakan desain komparatif non-eksperimental dan metodologi survei, penelitian ini menggunakan kuesioner resiliensi matematis dan gaya belajar sebagai instrumen pengumpulan data. Subjek penelitian terdiri dari 62 siswa sekolah dasar kelas lima dari Kota Stabat, Provinsi Sumatera Utara. Pengambilan sampel dilakukan dengan menggunakan teknik probability proportional sampling, menghasilkan 32 siswa perempuan dan 30 siswa laki-laki. Analisis data menggunakan uji ANOVA dua arah untuk menguji dampak dari dua variabel independen (gaya belajar dan jenis kelamin) terhadap variabel dependen (resiliensi matematis). Temuan penelitian mengungkapkan bahwa gaya belajar visual adalah gaya belajar yang paling umum (dominan) di antara siswa. Lebih jauh lagi, gaya belajar menunjukkan dampak yang signifikan pada resiliensi matematis, yang menunjukkan bahwa variasi dalam gaya belajar memberikan kontribusi secara substansial pada tingkat resiliensi matematis. Sebaliknya, tidak ditemukan pengaruh jenis kelamin pada resiliensi matematis. Selain itu, analisis menunjukkan tidak adanya interaksi antara gaya belajar dan jenis kelamin dalam mempengaruhi resiliensi matematis. Temuan ini menunjukkan bahwa gaya belajar secara mandiri mempengaruhi resiliensi matematis, tanpa moderasi apa pun oleh jenis kelamin. Implikasi dari penelitian ini menunjukkan bahwa ketika mempertimbangkan strategi pengajaran untuk meningkatkan resiliensi matematis, penekanan dapat diberikan pada gaya belajar individu tanpa perlu membedakan berdasarkan jenis kelamin.